Phylogeny and biogeography of Triportheidae (Teleostei: Characiformes) based on molecular data - Mariguela, T. C. [UNESP]; Roxo, F. F. [UNESP]; Foresti, F. [UNESP]; Oliveira, C. [UNESP] (Elsevier, 2016)
Triportheidae represents a relatively small family of characiform fishes with highly modified morphology. The relationship among characiform families is still unclear, and a phylogenetic analysis for the family including a representative number of Triportheus species has never been performed. Here, we inferred a phylogeny for 19 of the 22 species recognized for this family and two possible new Triportheus species using two mitochondrial and three nuclear genes. Our results show that (1) Triportheidae is monophyletic and a sister group of the clade consisting of the families Bryconidae and Gasteropelecidae; (2) Triportheus is monophyletic, but some species need to be reviewed and described; (3) all genera in Triportheidae, except for Agoniates originated in the period between Early Oligocene and Early Miocene and (4) speciation in Triportheidae coincides with important geological events in South America, reinforcing the importance of time-calibrated trees to study fish evolution.
Keywords: Evolution; Freshwater sardines; Molecular systematics; Neotropical fishes; Phylogeny